The role of syntax in the productivity of German N+N compounds. A diachronic corpus study - Kristin Kopf (Zeitschrift für Wortbildung)
This paper studies the morphological productivity of German N+N compounding patterns from a diachronic perspective. It argues that the productivity of compounds increases due to syntactic influence from genitive constructions ("improper compounds") in Early New High German. Both quantitative and qualitative productivity measures are adapted from derivational morphology and tested on compound data from the Mainz Corpus of (Early) New High German (1500–1710).